Comparison of the accuracy of intraoral scanning systems with conventional impression in dentate patient - ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (My University, 2020)
Background: Over the last years, different intraoral scanningsystems for direct digitalization have been introduced to the dentalmarket. However, the accuracy of these scanners is variable, andlittle information is available. The aim of this in vivo study was tocompare the accuracy of two intraoral scanning systems and thedifference between upper and lower jaw on the accuracy.Methods: 10 patients with full dentition received one conventionalimpression with polyvinyl siloxane (Elite HD+, Zhermack SpA, Italy)and three scans with CEREC OC (Sirona Dental Systems, Sirona,Bensheim, Germany) and Straumann CARES IOS (Intra oralScanner, Basel, Switzerland) for upper and lower jaw. Theconventional impressions were poured and the casts made from itwere scanned and used as the reference model to evaluateprecision and trueness of intraoral scanning virtual modelsprovided by each system. Digital models were analyzed with asoftware (Geomagic Control; Geomagic, Morrisville, USA).Results: The trueness value was 99.88±42.56 μm in upper jaw and82.6±26.81 μm in lower jaw for CEREC OC, and 105.53±25.49 μmin upper jaw, and 109.56±36.84 μm in lower jaw for CARES IOS.The differences between these two systems were not statisticallysignificant (P>0.05), but statistically significant difference wasfound in the precision (P<0.05). CEREC OC showed higher valuein both upper and lower jaws.Conclusion: CEREC OC was more precise than CARES IOS andat a similar level of trueness. No statistically significant differencewas found between upper and lower jaws in both systems

Amaç: Son senelerde, direkt dijitalizasyon için farklı intraoral_x000D_ tarama sistemleri ortaya çıkmıştır. Ancak bu tarayıcılarının_x000D_ doğruluğu değişkendir ve hakkındaki bilgiler yetersizdir. Bu_x000D_ çalışmanın amacı, iki farklı intraoral tarama sisteminin, alt ve üst_x000D_ çene arasındaki tarama doğruluğu farkının karşılaştırılmasıdır._x000D_ Gereç ve Yöntemler: 10 adet tam dişli hastanın her birinden bir_x000D_ adet PVS (Elite HD+, Zhermack SpA, İtalya) materyali ile ölçü_x000D_ alındı ve 3 adet alt-üst çene taraması CEREC OC(Sirona Dental_x000D_ Systems, Sirona, Bensheim, Almanya) ve Straumann CARES IOS_x000D_ (Intra oral Scanner, Basel, İsviçre) ile yapıldı. Konvansiyonel_x000D_ ölçüden elde edilen alçı modeller taratılarak referans model olarak_x000D_ netlik ve doğruluk kıyaslamasında kullanıldı. Netlik_x000D_ değerlendirilmesindeki deviasyonlar diğer ölçülerin birbiri üzerine_x000D_ çakıştırılması metodu ile gözlemlendi. Dijital ölçü dosyaları STL_x000D_ formatına dönüştürülerek (Geomagic Control; 3D Systems. ABD)_x000D_ işlendi ve analiz edildi._x000D_ Bulgular: Doğruluk değerleri, CEREC OC için üst çenede_x000D_ 99.88±42.56 μm alt çenede, 82.6±26.81 μm dir. CARES IOS için_x000D_ üst çene doğruluk değeri 105.53±25.49 μm, alt çene doğruluk_x000D_ değeri 109.56±36.84 μm dur. İki sistem arasındaki doğruluk_x000D_ değeri farkı istatistiksel olarak anlamlı değildir (P>0.05). Netliğin_x000D_ farkı istatiksel olarak anlamlıdır (P<0.05), CEREC OC alt ve üst_x000D_ çenede netlik açısından daha yüksek değerler gösterdi._x000D_ Sonuç: CEREC OC netlik olarak CARES IOS sisteminden daha_x000D_ üstün bulunurken, doğruluk seviyesi her iki sistemde de benzerdir._x000D_ Alt ve üst çeneler arasında her iki sistemde istatistiksel olarak_x000D_ anlamlı fark bulunmamıştır.
Tüm dişleri mevcut hastalarda konvansiyonel ölçü ve intraoral dijital taramanın netliğinin karşılaştırılması